Pre-operative, Intraoperative, and Post-operative Determinants Associated with 30-day Mortality Post-Coronary Artery Bypass Graft: A Retrospective Cohort Study - Rinaldi, Ikhwan; Sudaryo, Mondastri K.; Mansjoer, Arif (Open Access Macedonian Journal of Medical Sciences, 2022)
Abstract Background: Various determinants of 30-day mortality risk in CABG patients have been formulated into certain scoring models such as the EuroSCORE and ACEF model. However, these models only consider preoperative parameters while excluding intraoperative, postoperative, and perioperative parameters. Currently, the prior research has increasingly emphasized the role of these excluded parameters as determinants of post-CABG mortality. Furthermore, there are differences in mortality rate of CABG procedures in Indonesia when compared with other countries. Hence, this study aimed to identify preoperative, intraoperative, and postoperative determinants of 30-day mortality after CABG surgery in Indonesian population. Methods: In this retrospective cohort study, secondary data were obtained from the medical records of 263 patients aged ≥ 18 years who underwent CABG at a single center in Indonesia during the year 2012–2015. Selected preoperative, intraoperative, postoperative, and perioperative determinants were analyzed in both bivariate and multivariate Cox regression models to identify determinants associated with 30-day mortality. Results: The 30-day mortality rate after CABG was 11.8%. Multivariate analysis identified neurological dysfunction (HR 6.16; 95% CI 2.42-15.66), renal impairment (HR 3.9; 95% CI 1.46-10.38), left ventricle dysfunction (HR 3.53;95% CI 1.55-8.03), aortic clamp duration (HR 3.7;95% CI 1.53-8.96), surgery duration (HR 3.85;95% CI 1.39-10.70), postoperative thrombocytopenia (HR 3.99;95% CI 1.72-9.23), and postoperative intra-aortic balloon pump (HR 10.98; 95% CI 4.77-25.28) as significant determinants associated with 30-day mortality after CABG Conclusions: Neurological dysfunction, renal impairment, left ventricle dysfunction, aortic clamp duration, surgery duration, postoperative thrombocytopenia, and postoperative intra-aortic balloon pump were independent determinants for 30-day mortality after CABG.